Viewing the "New" South Africa. Representations of South Africa in Television Commercials - (:unkn) unknown (My University, 2006)
Apartheid was based on particular perceptions and hierarchical classifications of the human body. It aimed at separating people with different physical appearances in order to preserve the purity of the “white race” and its domination in South Africa. To understand the changes that have taken place in South Africa since 1990, to go beyond the surface of observable events and reach the social representations of these transformations that have developed among South Africans, the body, or more precisely images of the body, provide a good point of departure. The present study presents an experimental small scale survey aiming at uncovering social representations of the “new” South Africa shared by young South Africans at the dawn of the 21st Century. It argues that studies of social representations require, at least in their initial stage, the use of non-directive collective interviews; it shows that images of the body as displayed in TV commercials can be used as efficient prompts to start discussions about the present state of South African society. The survey used four commercials taped on South African TV in 2003; these clips were used as prompts in three non-directive collective interviews with young South Africans, to which was added a test group consisting of French students. TV commercials were analysed using methods inspired by the semiology of cinema; the transcripts of the interviews were analysed using methods borrowed from the French school of political sociology. The results of this experimental survey show that, if the transition from apartheid to a democratic non racial society is considered positive, it is perceived with ambivalences and sometimes contradictory feelings: the future of South Africa may at the same time be envisioned with great optimism and heavy anxieties; relations between South Africans can be described as harmonious and be lived amidst acute tensions. Ambivalences and tensions, which remain very often untold, are
Keywords: African Research